112. Low frequency repetitive transcranial magnetic stimulation in early phase of rehabilitation of patients with post-stroke aphasia. Issue 1 (January 2015) - Carrai, R.; Grippo, A.; Angelini, A.; Vettori, A.; Atzori, T.; Falsini, C.; Martini, M.; Pizzi, A.
<x xml:space="preserve">Abstract</x> About 50% of post-stroke patients remain aphasic a condition that greatly impede their reintegration to society. Results of Repetitive Transcranial Magnetic Stimulation (rTMS) as supplementary treatment for sub-acute post-stroke aphasia are controversial. We assessed the efficacy of inhibitory rTMS with conventional speech therapy to help recovery language performance in sub-acute stroke aphasia.In a randomised case-control double-blind study 12 non-fluent aphasic were consecutively enrolled. All patients suffered a first-ever stroke in the sub-acute stage defined as time since lesion onset from 1 month post-stroke. Patients were randomized either to receive real (low frequency on right-hemisphere homologue of Broca's area) or sham rTMS, to a 3-week (5 day in a week). Immediately after each rTMS all patients received speech therapy. The speech performance was evaluated with Italian version of Aachener Aphasia Test (AAT), before (T0) and after (T1) treatments.Seven patients were treated with real rTMS and 5 patients with sham rTMS. Total and sub totals AAT scores showed a similar improvement in real and in sham rTMS groups between T0 and T1.In early phase of rehabilitation (< 1 month) inhibitory rTMS over the right posterior inferior frontal gyrus, in combination with speech therapy, did not seem significantly to improve language recovery respect to conventional speech therapy only.